Exer-Gaming reduces fall risk and improves mobility after stroke - Memoona Aslam; Qurat ul ain; Pashmina Fayyaz; Arshad Nawaz Malik (Journal of the Pakistan Medical Association, 2021)
Objective: Major goal concealed behind conducting current study was to evaluate the effect of balance training via virtual reality in patients with chronic stroke having history of reduced global strength, reduced anticipatory balance and having history of fall. Methodology: A randomized control trial in which 30 chronic stroke survivors were recruited via purposive sampling technique was conducted. Sealed envelope method was used to randomly allocate patients into two groups that were Exer-gaming group (EGG) (n=15) and traditional training (TBT) group (n=15). Those patients having age above 50 were included using Modified Rankin Scale (MRS). Patients having cognitive deficits, severe contractures, unable to perform task, severe orthopedic condition of joint or those having fracture were not included in the study. The tools used to collect data included Berg Balance Scale (BBS), Timed Up & Go Test (TUG). The data was analyzed before starting the intervention and after every Continuous...